5(x+2)-3(x-4)=7-x

Simple and best practice solution for 5(x+2)-3(x-4)=7-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)-3(x-4)=7-x equation:


Simplifying
5(x + 2) + -3(x + -4) = 7 + -1x

Reorder the terms:
5(2 + x) + -3(x + -4) = 7 + -1x
(2 * 5 + x * 5) + -3(x + -4) = 7 + -1x
(10 + 5x) + -3(x + -4) = 7 + -1x

Reorder the terms:
10 + 5x + -3(-4 + x) = 7 + -1x
10 + 5x + (-4 * -3 + x * -3) = 7 + -1x
10 + 5x + (12 + -3x) = 7 + -1x

Reorder the terms:
10 + 12 + 5x + -3x = 7 + -1x

Combine like terms: 10 + 12 = 22
22 + 5x + -3x = 7 + -1x

Combine like terms: 5x + -3x = 2x
22 + 2x = 7 + -1x

Solving
22 + 2x = 7 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
22 + 2x + x = 7 + -1x + x

Combine like terms: 2x + x = 3x
22 + 3x = 7 + -1x + x

Combine like terms: -1x + x = 0
22 + 3x = 7 + 0
22 + 3x = 7

Add '-22' to each side of the equation.
22 + -22 + 3x = 7 + -22

Combine like terms: 22 + -22 = 0
0 + 3x = 7 + -22
3x = 7 + -22

Combine like terms: 7 + -22 = -15
3x = -15

Divide each side by '3'.
x = -5

Simplifying
x = -5

See similar equations:

| 8-7p=12-5p | | Y=sec(x^3) | | 8y+43-7y=75 | | 4c-5(x+1)+11=0 | | Y=3tan*4x | | x+(x*.0875)=20.12 | | 5(2x-7)=0 | | 2y+x=8.5 | | 2x^3+10x^2-2x-10=0 | | 6x+29=65 | | 4x=-2x-42 | | 3x+2.5=4x-35 | | 4(2-2y)+6=2(7+4y) | | 18x-3y=6 | | 2+2m=4m+5 | | -3x+3/5+1/5=2(4-x)/5 | | -13-(3m+4)= | | (1-u)(2u-7)=0 | | x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 | | 5x^2+18x-8=0 | | 2.5x+15+0.5(x-4)=1.2x+2(0.5x-6) | | 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 |

Equations solver categories